Crisis Management Policy of Natural Disaster - Sarjito, Aris (Advances in Social Sciences Research Journal, 2020)
Abstract Indonesia is the country that has the most active volcanoes in the entire world. The Eurasian Plate, the Pacific Plate, and the Indo-Australian Plate are three active tectonic plates that cause collision zones to form these volcanoes. Indonesia is estimated to have 129 volcanoes, all of which are carefully monitored by the Centre for Volcanology and Geological Disaster Mitigation. This is done because several volcanoes in Indonesia continue to show activity. Moreover, it is estimated that more than five million people live in the "danger zone" of a volcano where they must be immediately evacuated if the mountain shows significant upward activity (Indonesia-Investment, 2019). However, efforts to reduce the risk of natural hazards remain largely uncoordinated in different types of hazards and do not necessarily focus on areas with the highest disaster risk. This paper uses a descriptive qualitative approach as the main writing approach and uses crisis management theory by Rosenthal, that crisis management involves efforts: (1) to prevent a crisis from occurring; (2) to prepare better protection against the impact of crisis agents; (3) to make effective responses to the actual crisis; and (4) to provide plans and resources for post-crisis recovery and rehabilitation. The results of this study are: (1) to accelerate forest recovery, the government can engage the community with security and welfare approach; (2) natural disaster management is the main responsibility of the government; (3) In crises due to natural disasters, form a team that is responsive to critical situations. This team was formed by involving government agencies, community leaders, and NGOs; and (4) to increase the government's capacity to reduce the impact of natural disasters, assessment of potential damage, the establishment of an early warning system, and the improvement of disaster-resistant capabilities are needed. Keywords: Crisis Management; Natural Disaster; Policy.